Pain and Anxiety Reduction of First Stage Maternity Mothers using SEFT Intervention - Sri Mumpuni Yuniarsih; Helwiyah Ropi; Ida Maryati (LPPM Universitas Pekalongan, 2015)
Pain and anxiety are major problems in childbirth. Management of pain and anxiety made to smooth the process of childbirth. This study aimed to compare the effect of spiritual intervention and Spiritual Emotional Freedom Technique (SEFT) to reduce both pain and anxiety. The study design used was quasy experiment with consecutive sampling technique. The subjects involved were 36 mothers giving birth at health centers PONED Pekalongan which divided into two groups, SEFT intervention as intervension group and spiritual intervention as control group. The instrument used was numeric rating scale. Data were analyzed using the Mann Whitney U test, Wilcoxon and Independent t Test. The results showed there were differences in average decrease in pain and anxiety between two groups. SEFT intervention proven to reduce pain intensity of the first stage and maternal anxiety was better than spiritual intervention. Keywords: Anxiety, Pain childbirth, Spiritual Emotional Freedom Technique (SEFT).